Stage-specific survival rate of breast cancer patients in Northern Thailand in accordance with two different staging systems - Imjai Chitapanarux (2020)
© 2019 Asian Pacific Organization for Cancer Prevention. Objective: This study was attempted to investigate overall survival by stage at diagnosis in female breast cancer patients in Northern Thailand by using 2 different staging systems; namely, American Joint Committee on Cancer (AJCC) Tumor (T), Nodal (N) and Metastatic (M) staging system and Surveillance Epidemiology and End Results (SEER) summary staging system. Methods: We studies female breast cancer patients whose data were registered in Chiang Mai cancer registries between January 2006 and December 2015. Data were recorded in SEER summary staging system. The TNM AJCC staging was searched in the medical records. Results: A total of 3,873 female breast cancer patients were diagnosed from 2006-2015. All data sets were recorded in SEER summary stage 2000. Early stage was the most prevalent stage at the time of diagnosis (58%), followed by loco-regional advanced stage (32%), and metastatic breast cancer (10%). The 5-year overall survival rate of early, loco-regional advanced, and metastatic stages were 85.3%, 66.4%, and 26.2%, respectively. After examining the medical records, we excluded patients who had no data on T, N, and M in their records. Finally, only 3,251 patients were analyzed for AJCC stage-specific survival. The 5-year overall survival rate in stages I, II, III, and IV were 94.4%, 85.0%, 56.6%, and 28.3%, respectively. Conclusion: Comparing to more stable economic countries, the 5-year overall survival rate for a specific stage of breast cancer in Northern Thailand was slightly lower in early stage and stage I-II in accordance with AJCC, but much lower in loco-regional stage and stage III with respect to AJCC. Nevertheless, it was similar in metastatic stage and stage IV according to AJCC.